Designing a STEM-Based Learning Trajectory on Tangent Lines to Parabolas Using a Football Context for Pre-Service Teachers - Nopriyanti, Tika Dwi; Zulkardi; Ratu Ilma Indra Putri; Nyimas Aisyah (UNNES JOURNAL, 2025)
Understanding the concept of a tangent line to a parabola is an important topic but often a challenge for prospective mathematics teacher students when learning emphasizes procedures over conceptual understanding. This research aims to design a STEM-based learning trajectory (Hypothetical Learning Trajectory) to enhance students' mathematical flexibility skills. The research method uses design research with three stages: initial design, learning experiment (pilot and full implementation), and retrospective analysis. The research subjects consisted of pre service mathematics teacher students from two classes. The learning path includes three STEM activities: exploring the crossbar challenge video in soccer, algebraic analysis and visualization using Desmos, and constructing and verifying tangents analytically and graphically. Data were obtained through classroom observation, interviews, worksheets, and videos, and were analyzed qualitatively using triangulation and the constant comparison method. The results show that students move from intuitive reasoning toward formal understanding thru transitions in contextual, symbolic, and graphical representations. Revising the HLT results in a Local Instructional Theory (LIT) that strengthens students' thinking flexibility and conceptual understanding. The results suggest that subsequent studies could refine and implement this LIT across diverse mathematical topics or STEM-integrated learning environments to examine its broader impact on students’ representational and reasoning flexibility. Abstrak Pemahaman tentang konsep garis singgung pada parabola merupakan topik yang penting namun sering menjadi tantangan bagi mahasiswa calon guru matematika ketika pembelajaran lebih menekankan pada prosedur daripada pemahaman konseptual. Penelitian ini bertujuan untuk merancang lintasan belajar berbasis STEM (Hypothetical Learning Trajectory) guna meningkatkan kemampuan fleksibilitas matematis mahasiswa. Metode penelitian yang digunakan adalah design research yang terdiri atas tiga tahap: desain awal, eksperimen pembelajaran (uji coba awal dan implementasi penuh), serta analisis retrospektif. Subjek penelitian terdiri atas mahasiswa calon guru matematika dari dua kelas. Lintasan belajar yang dikembangkan meliputi tiga aktivitas berbasis STEM, yaitu mengeksplorasi video crossbar challenge dalam sepak bola, melakukan analisis aljabar dan visualisasi menggunakan Desmos, serta membangun dan memverifikasi garis singgung secara analitik dan grafis. Data diperoleh melalui observasi kelas, wawancara, lembar kerja mahasiswa, dan rekaman video, kemudian dianalisis secara kualitatif dengan teknik triangulasi dan metode perbandingan konstan. Hasil penelitian menunjukkan bahwa mahasiswa mengalami pergeseran dari penalaran intuitif menuju pemahaman formal melalui transisi representasi kontekstual, simbolik, dan grafis. Revisi terhadap HLT menghasilkan Local Instructional Theory (LIT) yang memperkuat keluwesan berpikir dan pemahaman konseptual mahasiswa. Hasil ini juga menunjukkan bahwa penelitian lanjutan dapat menyempurnakan dan mengimplementasikan LIT tersebut pada berbagai topik matematika atau lingkungan pembelajaran berbasis STEM untuk menelaah dampak yang lebih luas terhadap fleksibilitas representasional dan penalaran mahasiswa.